Peranan Wakaf Dalam Pembangunan Infrastuktur Di Kecamatan Peukan Bada Aceh Besar - Edi Saputra; Yuliana Yuliana; Rizky Akbar (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
Abstract: Waqf is one of the economic instruments of Muslims in an effort to improve the welfare of the community. There are two important aspects in the effort to carry out waqf, namely the spiritual and material aspects. These two aspects have an important role in the life of people who are Muslim throughout the world. When in the category of ownership rights, waqf is included in the rights of al-Intifᾱq. There are several types of waqf including stock waqf, cash waqf, corporate waqf and so on. The Aceh government needs to carry out every effort to build the economy starting from cities, villages and the region as a whole which has suffered a setback due to war and the Tsunami. The initial steps that must be taken are, such as explaining the interests and contributions of waqf to the economy on community, which will give a positive impression to the waqf institution itself. Every problem or obstacles must be viewed with full prudence so that society is not burdened in implementing waqf, and what is more important is the awareness of individual Muslims to carry out waqf in line with the interests of improving the socio-economic and infrastructure of Muslims. When the available waqf assets need to be developed so that they can be utilized by each individual.